Terms Defining The Names Of Soil, Minerals And Other Raw Materials Used In Rishton Pottery - Mamatkulova Zilola Rejabaliyevna (Euro Asian Journal Publishing, 2024)
In this article, the terms used in the pottery process, including the terms meaning soil, substance-mineral and other raw materials, are systematically and structurally approached, and they are etymologically researched. The terms meaning soil types are explained with the help of examples.
Keywords: Soil; etymological dictionary; explanatory dictionary